Courtesy and Politeness in Sir Gawain and the Green Knight - Jucker, Andreas H. (Studia Anglica Posnaniensia, 2015)
A close reading of three selected passages of the Middle English alliterative romance Sir Gawain and the Green Knight provides a detailed picture of fictional and fairy-tale manifestations of courtly and polite behaviour in Middle English, a period that imported many new terms of courtesy and politeness from French. In the three passages Sir Gawain is visited in his bedchamber by the lady of the house, who tries to seduce him and thus puts him in a severe dilemma of having to be courteous to the lady and at the same time loyal to his host and to the code of chivalry. The analysis shows how Sir Gawain and the lady of the house engage in a discursive struggle of the true implications of courteous behaviour. It also shows how the two characters use nominal and pronominal terms of address to negotiate their respective positions of power, dominance and submission towards each other. And, finally, an analysis of requests reveals how the lady carefully selects appropriate strategies to reflect the severity of the imposition of her requests and her momentary standing in their discursive struggle.